Healthcare alarm system - Ng, Xue Ting (2015)
Have you ever wonder what if Singapore has an over number of elderly people? According to the statistics of old-age support ratio, the numbers continued to fall. There were 6.0 residents aged 20-64 years for each resident aged 65 years and over in 2014, a decline from 6.4 in 2013. With this rapidly aging population in Singapore, it also means that the number of elderly who are suffering from diseases will increase tremendously. For those elderly people who are staying alone, their health conditions began to gain the outmost concern from their doctors and family members. Hence, there is a need to design and develop a reliable, low cost healthcare alarm system to measure and monitor their pulse rate and implement a healthcare alarm system to send information via SMS out to the doctor and family members if abnormal pulse rate is detected. As there will be an increased number of elderly in Singapore, an effective and useful healthcare alarm system is highly desired towards today’s society. The 1st main significant feature of the healthcare alarm system is that it uses Arduino Software as its operating system to program the Arduino Uno Controller. When the heart pulse detects an abnormal heart rate or high temperature from the patient/elderly, it will automatically send out an SMS through the 4G networks to the hospital doctors and the patient/elderly family members. Another significant feature is that as 4G network is expected to be available in most of the places, Internet services are readily available everywhere. Thus the health care system can upload information and the details of the patient/elderly to a web page. When the doctors and family members wish to monitor their health conditions, they can connect to a web page via Internet or mobile apps. With this health care alarm system, it can benefit both the doctors and family members when the elderly/patient is alone at home as the safety of the elderly/patient was taken care of. This kept the overall cost down yet gave a great performance. In this report it records and depicts what the student have learned and done over the 2 semesters which includes areas like brainstorming which ideas to use, researching, understanding how to program using Matlab software and Arduino software, troubleshooting for both hardware and software, also the steps and implementation of the whole project.